The Role of the Top 50 US Cargo Airports and 25 Air Cargo Airlines in the Logistics of E-Commerce Companies - Florido Benítez, Lázaro (IOAP-MDPI, 2023)
Background: The purpose of this study is to analyse the role of the main 50 US cargo airports and 25 air cargo airlines in the logistics of e-commerce companies from 2000 to 2020, to highlight the importance of airports in the logistics and e-commerce industries. Methods: A review of the relevant literature on airports, air cargo carriers, logistics, and e-commerce sectors was undertaken to understand the link between them. The data were collected using four criteria: airport category, airport location, top 25 air cargo carriers, and other relevant data from the Federal Aviation Administration, International Air Transport Association, Organization for Economic Co-operation and Development, US Department of Transportation, amongst many others. Results: The findings reveal that there is a consolidated relationship between airports, air cargo airlines, and e-commerce, which has been especially evident during the COVID-19 pandemic. Airports and air cargo carriers are identified as the most relevant partners in the e-commerce industry. This is because of the e-commerce sector and its users’ demand for speed and reliability in the interaction between the demand for and supply of products and services. Conclusions: The pandemic has changed the way in which organizations operate and is likely to create new demand from companies and users in the aviation and e-commerce industries. E-commerce companies are highly dependent on the quality and efficiency of air cargo airlines and airports because they need to provide a good shipping service for their products to customers.
Keywords: Aeropuertos; Airport; Air cargo airlines; Logistics; Location; Connectivity; E-commerce companies; Airport reputation; Retail; Distribution